2019
DOI: 10.3390/nu11092213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Young Child Formula in Ensuring a Balanced Diet in Young Children (1–3 Years Old)

Abstract: During the nutritional vulnerable period of 1–3 years of age, nutrient intake is often inadequate due to an unbalanced diet. Young child formula (YCF) has been proposed as a means of improving nutrition in this age group. We compared the food consumption and nutrient intake of 241 YCF consumers (YCF-C) to those of 206 non-consumers (YCF-NC), selected from among the children enrolled in the Nutri-Bébé survey, an observational cross-sectional survey, conducted from 3 January to 21 April 2013. Food consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 35 publications
6
29
0
Order By: Relevance
“…In contrast to the expert opinions and recommendations on toddler milk and YCM from Europe and the U.S. [13,[26][27][28], the routine use of YCM is not deemed a necessity, as the missing nutrients in the diet of young children can also be provided by other dietary sources in these countries, the findings of the current study did support the role of YCM in the diet of young children in the Philippines. Furthermore, our study also supported that the use of YCM/PCM can increase the intake of iron and vitamin D and decrease the intake of protein when compared to other milk, in accordance to the European Food Safety Authority (EFSA) scientific opinion [26], conclusion from the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) committee [13], and findings from previous studies [5][6][7][8][9][10][11].…”
Section: The Role Of Ycm/pcm In the Diet Of Filipino Childrensupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast to the expert opinions and recommendations on toddler milk and YCM from Europe and the U.S. [13,[26][27][28], the routine use of YCM is not deemed a necessity, as the missing nutrients in the diet of young children can also be provided by other dietary sources in these countries, the findings of the current study did support the role of YCM in the diet of young children in the Philippines. Furthermore, our study also supported that the use of YCM/PCM can increase the intake of iron and vitamin D and decrease the intake of protein when compared to other milk, in accordance to the European Food Safety Authority (EFSA) scientific opinion [26], conclusion from the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) committee [13], and findings from previous studies [5][6][7][8][9][10][11].…”
Section: The Role Of Ycm/pcm In the Diet Of Filipino Childrensupporting
confidence: 88%
“…Young children milk (YCM) and preschool children milk (PCM), are milks tailored for children's nutritional needs at different age stages, fortified with vitamins and minerals, some with DHA and probiotics. A number of observational studies and randomized controlled trials (RCT) in Europe and Australia and New Zealand have demonstrated that, when compared to cow's milk, YCM improved nutrient intakes among children above 12 months, particularly in iron and vitamin D [5][6][7][8][9]. Several studies have shown that children who consumed YCM had better iron and vitamin D status than non-consumers [7,10,11], and it had a lower percentage of body fat than children who consumed cow's milk [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested as a resource to help to achieve adequate intakes of critical nutrients in young children. They are fortified with several nutrients, including iron, vitamin D and essential fatty acids (EFA) and they contain less protein, saturated fat and sodium than CM [10]. Also, according to the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) the YCF can be used as part of a strategy to increase the intake of iron, vitamin D and n-3 PUFA and decrease the intake of protein compared with unfortified CM [11].…”
Section: Introductionmentioning
confidence: 99%
“…The total annual volume of infant adapted milk accounts for 57 million liters [12]. Nevertheless, currently, there is some controversy about the advantages or disadvantages of drinking YCF or CM between 1-3 years old and whether the use of fortified milk formulas in later ages represents a nutritional advantage versus the exclusive use of cow's milk [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Chouraqui et al, 2019, 73 conducted a controlled multicenter study with almost 1,000 children aged between 1 and 3 years old. Children < 2 years old using YCF consumed lower amounts of protein and sodium than those who consumed cow's milk.…”
Section: Studies On the Use Of Young Child Formula And Its Results Inmentioning
confidence: 99%